2008
DOI: 10.1080/13548500802241928
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in medical students' attitudes towards male and female rape victims

Abstract: This study examines attitudes toward female and male rape victims (ARVS, Ward, 1988) among UK medical students (N=240; 120 female and 120 male). The study's hypotheses, namely that male respondents will view rape victims more negatively than female respondent and that male victims will be viewed more negatively than female victims, were supported. Implications of the findings in relation to the inclusion of sexual violence teaching in UK medical undergraduate curricula, and suggestions for further research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 29 publications
2
32
0
1
Order By: Relevance
“…Early research found that medical students make similar blame attributions as other student samples (Gilmartin-Zena, 1983). Findings indicated that although low levels of culpability were assigned to victims, victim blaming was still present, especially among male observers (Gilmartin-Zena, 1983); and these results have also been supported by more recent research (Anderson & Quinn, 2009). Another early study by Alexander (1980) investigating nurses' victim blame judgments indicated that nurses portray similar blame attributions for victims of violent crimes on the one hand and rape victims on the other hand.…”
Section: Observer Professional Statussupporting
confidence: 65%
“…Early research found that medical students make similar blame attributions as other student samples (Gilmartin-Zena, 1983). Findings indicated that although low levels of culpability were assigned to victims, victim blaming was still present, especially among male observers (Gilmartin-Zena, 1983); and these results have also been supported by more recent research (Anderson & Quinn, 2009). Another early study by Alexander (1980) investigating nurses' victim blame judgments indicated that nurses portray similar blame attributions for victims of violent crimes on the one hand and rape victims on the other hand.…”
Section: Observer Professional Statussupporting
confidence: 65%
“…It is argued that male rape myths are prevalent among the general public as well as counsellors, medical professionals, and law enforcement (Anderson & Quinn, 2009). Chapeau et al (2008) found that participants equally endorsed male rape myths and female rape myths and that there was a strong, positive relationship between participants' endorsement of these two types of myths.…”
Section: Common Male Rape Myths In the Wider Communitymentioning
confidence: 99%
“…The published literature suggests that many civilian police officers are not prepared to assist male sexual assault victims and may hold negative attitudes toward male victims (Javaid, 2014(Javaid, , 2017. Medical students view male sexual assault victims more negatively than female victims (Anderson and Quinn, 2009). In addition, qualitative research with male civilian victims reveals that some have negative experiences with service providers, including dismissive treatment from social workers and counselors, insensitivity from police, and poor treatment by medical professionals ( Washington, 1999).…”
Section: Expectations Of Negative Consequences For Disclosurementioning
confidence: 99%
“…Researchers recommend that the curriculum used to train military service providers include factual information about male sexual assault and address common myths about sexual assault against men and women ( Anderson and Quinn, 2009;Kassing and Prieto, 2003). If service providers build a factual foundation of information about male sexual assault and understand the potential impact of false beliefs on male victims, they will be in a better position to counter the harmful rape myths that victims may believe about themselves (e.g., "I should have been able to stop it") and that others might believe about them (Davies, 2002).…”
Section: Meeting Male Victim Needs Through Provider Preparationmentioning
confidence: 99%
See 1 more Smart Citation